Author Correction: 2600-years of stratospheric volcanism through sulfate isotopes - E. Gautier (Nature Portfolio, 2019)
The authors became aware of a mistake in the data and axis labeling in Fig. 2 in the original version of the Article. Specifically, the authors mistakenly copied and pasted a formula for background correction instead of the actual values. As a result of this, Fig. 3 was updated to replace the incorrect label ‘sulfate flux (kg km−2)’ with the correct ‘sulfate concentrations (ng g−1)’ on the far-left y-axes in both panels, and to add the correct data for Δ33S, as given by the red dotted lines. The correct version of Fig. 3 is shown below as Fig. 1, which replaced the previous incorrect version, shown below as Fig. 2. This has been corrected in both the PDF and the HTML versions of the Article. The findings and interpretations in the original Article are based on the correct dataset, and this error does not affect the original discussion or conclusions of the Article. The authors apologize for the confusion caused by this mistake.